2015
DOI: 10.3109/14397595.2015.1031444
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for the use of mycophenolate mofetil for adult patients with lupus nephritis in Japan

Abstract: MMF was commonly used for the treatment of adult LN patients with acceptable efficacy and safety in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The dose of MMF initially used, according to the study design, was based on previous work in autoimmunity . From our previous pilot study, we observed that even low doses of MMF (1000 mg/d) were effective at suppressing orbital inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…The dose of MMF initially used, according to the study design, was based on previous work in autoimmunity . From our previous pilot study, we observed that even low doses of MMF (1000 mg/d) were effective at suppressing orbital inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…In the present surveillance study, the efficacy of MZR was confirmed based on composite indicators. Numerous reports have been published recently showing that MMF and tacrolimus are effective in terms of providing satisfactory improvements in urine protein [17][18][19]. In the present study, decreases in urine protein levels were also confirmed, and the efficacy of MZR was demonstrated.…”
Section: Efficacysupporting
confidence: 81%
“…In Japan, a multicenter surveillance study (2008-2013) conducted in 137 adult patients with LN by the Japanese College of Rheumatology on the status of MMF use in everyday medical practice reported that MMF has acceptable efficacy and safety, and that it was used in combination with another immunosuppressant in nearly half of the patients; specifically, it was used concomitantly with tacrolimus in 35.7% of the patients [18]. Furthermore, it has been reported that MZR can be used with tacrolimus [26,27].…”
Section: Multi-target Therapymentioning
confidence: 99%
“…The dose can be adjusted according to age and symptoms, but the maximum daily dose is 3000 mg for adults and 2000 mg for children. The dosage is based on the results of a survey conducted in Japan [ 13 , 14 ] prior to the approval. The doses of MMF used in patients with primary nephrotic syndrome in the database were generally within the approved dose range for lupus nephritis and transplant-related diseases in Japan, and most patients were treated with a daily dose of 2000 mg or less.…”
Section: Discussionmentioning
confidence: 99%